Supporting clinical research professionals through educational innovations - Lee-Chavarria, Diana; Loucks, Tammy L.; Paranal, Rechelle; Sampson, Royce; Feghali-Bostwick, Carol (Frontiers in Pharmacology, 2024)
Clinical Research Professionals (CRPs) are essential members of the Clinical & Translational Research Workforce. Many academic medical institutions struggle to recruit and retain these vital team members. One strategy to increase job satisfaction and promote the retention of CRPs is through educational initiatives that provide training and professional development. The South Carolina Clinical and Translational Research (SCTR) Institute Workforce Development (WD) team at the Medical University of South Carolina (MUSC) developed several trainings as part of our larger educational portfolio for CRPs. In 2022 WD implemented a digital badge micro-credential for SCTR's Core Clinical Research Training (CCRT) course in collaboration with institution-wide education and technology offices. Beginning in January 2023, individuals were able to earn the CCRT Certified Digital Badge upon successful completion of the CCRT course.